After the Paris agreement: New challenges for the EU's leadership in climate policy - Susanne Dröge; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2016)
In December 2015, 195 countries adopted a new global climate agreement in Paris. It provides an expanded regulatory framework and specifies the goals of the UN Framework Convention on Climate Change (UNFCCC). A significant number of states including the U.S. are expected to ratify the Paris Agreement (PA) within the year. Industrialized nations have a strong obligation to keep up the momentum that was generated in Paris. If the European Union (EU) wants to maintain its leadership role, it should focus on two key tasks in 2016. First, it should speed up legislation to implement the climate and energy targets for 2030 adopted by the European Council, a political prerequisite for Member States' ratification of the PA. Second, it should expand and strengthen cooperation with the developing countries. For the immediate future, an increase in EU climate ambitions for 2030 or 2050 is not likely to become part of the political agenda. (SWP Comments)
Keywords: 320